Optical and structural study of graphane-like materials obtained by CVD method - Assubayeva, M.A.; Bilbayev, I.M.; Nemkayeva, R.R.; Guseinov, N.R.; Kudryashov, V.V. (Recent Contributions to Physics, 2015)
At the moment obtaining of large area graphene samples is animportant issue great need due to the wide potential applications of this material with with exceptionally high physical performance. Whereas micromechanical cleavage is a laboratory method for graphene studying, different methods are being offered for controlled obtaining of big sized structures. One of this methods is chemical vapour deposition (CVD). In this paper results of graphene samples production by CVD method, as well as studies of its samples using optical microscopy, Raman spectroscopy, opticalsprectrophotometry are performed. Furthermore, connection of graphene with hydrogen, named as graphene attracts the great interest. Owing to the ability to control band gap of graphane-like structures there is the perspective of their use in electronic devices. Furthermore, there is the possibility of their use as solid carriers of hydrogen in hydrogen energy.